Analysis Of Defect Waste Reduction In Metal Forming Process Using Lean Six Sigma - Hassan Rahmatillah; Rusindiyanto Rusindiyanto (ITEJ (Information Technology Engineering Journals), 2025)
This study investigates the reduction of defect waste in the metal forming process at PT XYZ, with a specific focus on the production of the reff D nose component. Recognizing the critical importance of quality in the aerospace industry, where even minimal defects can compromise safety and operational integrity, this research applies Lean Six Sigma methodology to address the observed defect rate, which averaged 4.6% over the period 2018–2023—significantly exceeding the company’s target of 1%. A comprehensive DMAIC (Define, Measure, Analyze, Improve, Control) framework was employed to systematically identify, quantify, and analyze the sources of defects. Data were collected from both primary sources, including direct observations and stakeholder interviews, and secondary sources such as production records and defect reports. Advanced tools such as SIPOC diagrams, Pareto analysis, Interpretive Structural Modeling (ISM), and the 5 Whys method for Root Cause Analysis (RCA) were utilized to determine the critical factors affecting process performance. The analysis revealed that issues related to raw material quality, suboptimal process parameter settings, machine conditions, operator competency, and production environment stability are the primary contributors to the elevated defect rates. Based on these findings, targeted improvement strategies were proposed to optimize process efficiency and enhance product quality.